(untitled) (Journal of Health, Population and Nutrition, 2011)
Determination of vitamin D status in different age-groups in a community and in different climates of a country is necessary and has important implications for general health. The study was conducted to determine the prevalence of vitamin D deficiency among the adult population of Isfahan, a centrallylocated city in Iran. In this cross-sectional study, 1,111 healthy people-243 men and 868 women-aged 41.4 (mean 14 and range 20-80) years, who attended a single-consultation outpatient clinic, were selected. Serum 25-hydroxy vitamin D (25-OHD), parathyroid hormone (PTH), calcium and phosphorus concentrations were measured. Mild, moderate and severe vitamin D deficiencies were defined as 25-OHD values of 20-30 ng/mL, 10-20 ng/mL, and <10 ng/mL respectively. The median (range) concentrations of 25-OHD were 21 (4.0-105.0) ng/mL in males and 18 (1.5-117) ng/mL in females (p=0.05). The prevalence of mild, moderate and severe vitamin D deficiencies among the adult population was 19.6%, 23.9%, and 26.9% respectively. Vitamin D deficiency was more prevalent among women (p=0.001) and younger age-group (p=0.001). Medians of 25-OHD in spring-summer and autumn-winter were 21 ng/mL and 18 ng/mL respectively (p=0.005). The prevalence of severe vitamin D deficiency was higher in autumn-winter than in spring-summer (odds ratio=1.6, 95% confidence interval 1.2-2.2, p=0.001). The prevalence of vitamin D deficiency was high in a sunny city-Isfahan- especially among women and younger population. The high prevalence of vitamin D deficiency in this city emphasizes the necessity of vitamin D supplementation as more exposure to sun is limited due to the type of clothing required by current law. Key words: Adult; Cross-sectional studies; Parathyroid hormone; Seasonal variation; Vitamin D deficiency; Iran DOI: http://dx.doi.org/10.3329/jhpn.v29i2.7857 J HEALTH POPUL NUTR 2011 Apr;29(2):149-155